Queuing algorithm for speculative Network Processors. (2nd May 2007) - Foag, Jurgen; Wild, Thomas
This paper presents a queuing algorithm which is tailored for usage in speculative Network Processors (NPs). The queuing system uses Weighted-Fair Queuing queues (WFQ) which are extended by Priority Queues (PQ). While WFQ represents a common implementation in current routers supporting differentiated services, PQs allow to compensate extended protocol processing times due to mispredictions in a speculative system. When applying this concept, the generation of delay-jitter which would limit applicability of speculative packet processing for Real-Time (RT) traffic can be avoided. Utilising the presented queuing system in conjunction with speculative protocol processing in an NP, a latency reduction of up to 14.9% can be achieved compared to systems which support traditional packet processing methodologies.